2017
DOI: 10.4236/as.2017.810077
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Fertilization and Inoculation Effects on Dry Bean

Abstract: Dry bean (Phaseolus vulgaris L.) has the ability to form symbiotic relationships with N 2 -fixing bacteria. The research objectives were to evaluate yield and growth differences between dry bean cultivars from black, navy, and pinto market classes, with different N management combinations utilizing urea fertilizer, and two rhizobacteria inoculants. Research was conducted near Park River and Prosper, ND, during 2010, 2012. The experiment was a RCBD 3 × 2 × 3 factorial with four replicates with three dry bean cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
(17 reference statements)
1
1
0
1
Order By: Relevance
“…Furthermore, a lower concentration of available nitrogen in the soil serves as a driving force that stimulates plants to form root nodules in order to fix atmospheric nitrogen after receiving an initial nitrogen boost at the beginning of cultivation to meet the plant and microbial nitrogen requirements before nodule formation. This aligns with the findings of Buetow et al (2017) and Zoffoli et al (2021), who observed that nitrogen fertilization reduces the number of effective bacterial nodules on plant roots. Depending on genetic material, this difference may be attributed to the genetic composition of the cultivars in their response to available nitrogen and the plant's biochemical processes that supply the root nodules with the necessary food and energy for their formation (Etemadi et al 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, a lower concentration of available nitrogen in the soil serves as a driving force that stimulates plants to form root nodules in order to fix atmospheric nitrogen after receiving an initial nitrogen boost at the beginning of cultivation to meet the plant and microbial nitrogen requirements before nodule formation. This aligns with the findings of Buetow et al (2017) and Zoffoli et al (2021), who observed that nitrogen fertilization reduces the number of effective bacterial nodules on plant roots. Depending on genetic material, this difference may be attributed to the genetic composition of the cultivars in their response to available nitrogen and the plant's biochemical processes that supply the root nodules with the necessary food and energy for their formation (Etemadi et al 2019).…”
Section: Discussionsupporting
confidence: 92%
“…In fact, inoculation of soybean with B. japonicum increases biological nitrogen fixation and nitrogen uptake [29]. Our results are substantiated by those of Buetow et al [30,31], who found that Rhizobium inoculation of common bean improved the number of root nodules compared to uninoculated plants. A study conducted in Iran indicated that inoculating seeds of common bean with Rhizobium phaseoli resulted in an improvement in plant productivity and quality.…”
Section: Discussionsupporting
confidence: 88%
“…To increase SNF, dry bean growers can treat seeds with Rhizobium inoculants; however, inoculation studies have had mixed results. For example, recent studies have shown no increase in seed yield (Buetow et al, 2017; Cardillo et al, 2019; Dwivedi et al, 2015), and others have shown strong positive responses to inoculations (Hardarson, 1993; Martínez‐Romero, 2003; Mendoza‐Suárez et al, 2020). There is currently no consensus as to what causes this variation.…”
Section: Dry Beans and Agricultural Sustainabilitymentioning
confidence: 99%